COMPARATIVE ANALYSIS OF STOCK EXCHANGE PERFORMANCE WITH MACROECONOMIC INDICATORS BETWEEN INDONESIA AND MALAYSIA - Nangka, Michelle Inri Fifalia; Pangemanan, Sifrid S.; Pandowo, Merinda (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Growth of economy on the country shows the growth of the country. It can be seen from several elements. Stock market is one of the elements that play the vital role of economic. Stock market has purpose to play the important thing of economic and industry growth of the country and also as a measurement that the sector industry growth well as the growth of economy with their performance. There are several macroeconomic indicators used to compare the stock exchange performance between two countries. This study aimed to compare stock exchange performance based on macroeconomics indicators such as inflation of Consumer Price Index (annual %), Real Interest rate and PPP conversion factor (GDP) to market exchange rate ratio between two countries namely Indonesia and Malaysia during the period of year 2003 until 2012. The type of this research is comparative study with secondary data collection techniques. Independent Sample t-test was used to test the average difference. The conclusion of this study is there is a different of stock exchange performance between Indonesia and Malaysia that based on inflation. There is no different of stock exchange performance between Indonesia and Malaysia based on interest rate and exchange rate. Keywords: stock exchange performance, inflation, interest rate, exchange rate